MANAGEMENT OF ATHLETES WITH TYPE 2 DIABETES – THERAPEUTIC AND EDUCATIONAL STRATEGIES IN CLINICAL PRACTICE - Adam Żuczek; Olga Żuczek; Kinga Dyndał; Marcelina Broda; Patrycja Jędrzejewska-Rzezak; Katarzyna Urbańska; Izabela Szczap; Anna Hawryluk; Kamil Marzec; Aleksandra Mokrzycka (International Journal of Innovative Technologies in Social Science, 2025)
Purpose of the study: The aim of this literature review is to synthesize current knowledge on the clinical management of athletes with T2DM, focusing on pharmacological strategies, exercise recommendations, nutritional interventions, self-monitoring technologies, and interdisciplinary education to ensure safety and performance optimization.Materials and methods: A literature review was conducted using databases such as PubMed, Google Scholar, and Scopus. Articles published between 2000 and 2024 were included if they addressed physical activity, training strategies, medication management, or patient education in individuals with T2DM—particularly in athletic or physically active populations. Key publications included guidelines from the American College of Sports Medicine (ACSM), American Diabetes Association (ADA), and peer-reviewed reviews from Diabetes Spectrum, MDPI Sports, and Medical Sciences Sports Exercise.Results: The reviewed literature confirms that regular physical activity improves insulin sensitivity and glycemic control in patients with T2DM. However, exercise regimens must be personalized to avoid glycemic complications. Pharmacotherapy should consider the risk of hypoglycemia and dehydration, especially when using insulin or SGLT2 inhibitors. Nutritional strategies, such as pre-exercise carbohydrate intake and hydration protocols, are critical. Technological tools like continuous glucose monitoring (CGM) enhance real-time decision-making. Multidisciplinary education increases adherence and safety in diabetes care among athletes.Conclusions: Athletes with T2DM can achieve excellent glycemic control and high levels of performance if therapeutic strategies are personalized, evidence-based, and supported by education and technology. Further clinical studies are needed to develop sport-specific recommendations for this unique population.